TRANSFORMATION OF TEACHING METHODS: TECHNOLOGY TRAINING TO ENCOURAGE STUDENTS' MOTIVATION - Hapsari, Fitri Senny; Ahyar, Miftahul Farid Mochamad; Yusup, Ayi Ahmad Maulana (Universitas PGRI Sumatera Barat, 2024)
This community service initiative aims to enhance the technological proficiency of tutors at Gama UI Tutoring, Pondok Labu, Jakarta, via training and mentorship. This exercise involves instructors in an interactive and collaborative learning process utilizing Participatory Action Research (PAR) methodologies. This program encompasses workshops on technology-based learning media, assistance in creating digital teaching materials, and sessions for sharing experiences. The results of this activity revealed that tutors exhibited enhanced confidence in employing technology to augment student motivation and engagement. This initiative is anticipated to markedly enhance the quality of instruction at Gama UI Tutoring and foster innovation in pedagogical methodologies.Keywords: technological proficiency, tutors, students’ motivation